New role for the anandamide metabolite prostaglandin F2α ethanolamide: Rolling preadipocyte proliferation - Besma Boubertakh; Olivier Courtemanche; David Marsolais; Vincenzo Di Marzo; Cristoforo Silvestri (Journal of Lipid Research, 2023)
White adipose tissue regulation is key to metabolic health, yet still perplexing. The chief endocannabinoid anandamide metabolite, prostaglandin F2α ethanolamide (PGF2αEA), inhibits adipogenesis, that is, the formation of mature adipocytes. We observed that adipocyte progenitor cells—preadipocytes—following treatment with PGF2αEA yielded larger pellet sizes. Thus, we hypothesized that PGF2αEA might augment preadipocyte proliferation. Cell viability MTT and crystal violet assays, cell counting, and 5-bromo-2′-deoxyuridine incorporation in cell proliferation ELISA analyses confirmed our prediction. Additionally, we discovered that PGF2αEA promotes cell cycle progression through suppression of the expression of cell cycle inhibitors, p21 and p27, as shown by flow cytometry and qPCR. Enticingly, concentrations of this compound that showed no visible effect on cell proliferation or basal transcriptional activity of peroxisome proliferator-activated receptor gamma could, in contrast, reverse the anti-proliferative and peroxisome proliferator-activated receptor gamma-transcription activating effects of rosiglitazone (Rosi). MTT and luciferase reporter examinations supported this finding. The PGF2αEA pharmaceutical analog, bimatoprost, was also investigated and showed very similar effects. Importantly, we suggest the implication of the mitogen-activated protein kinase pathway in these effects, as they were blocked by the selective mitogen-activated protein kinase kinase inhibitor, PD98059. We propose that PGF2αEA is a pivotal regulator of white adipose tissue plasticity, acting as a regulator of the preadipocyte pool in adipose tissue.